Identification of Actinomyces viscosus from canine infections. - Davenport, A A (1975)
Actinomyces viscosus is a gram-positive, non-acid-fact, facultative, catalase-positive, filamentous, or diphtheroidal microorganism. It was isolated from six canine infections during a period of 1.5 years. The organism was cultured from exudate and flaky granules aspirated from infectious granulomas and empyemas. All cultures grew well aerobically and anaerobically with the addition of 10% carbon dioxide. They fermented lactose, produced catalase and acetylmethylcarbinol, reduced nitrates, hydrolyzed aesculin, and did not produce gelatinase or urease. These physiological characteristics distinguish A. viscosus from other morphologically similar organisms.